Meningkatkan Kemampuan Sosial Emosional Anak Melalui Metode Bermain Peran Pada Kelompok B Parado - Nurma Nurma; Hendra Hendra; Muslim Muslim; Ahmadin Ahmadin (Program Studi Bimbingan dan Konseling, 2024)
This study originates from the initial observation results indicating that the social-emotional abilities of group B children at Parado Kindergarten are significantly limited. They tend to struggle in controlling their emotions, easily get angry, and frequently engage in aggressive behaviors towards their peers. Additionally, they seldom apologize for their mistakes and appear to be indifferent to the consequences of their actions. Considering these challenges, the aim of this research is to evaluate the effectiveness of role-playing methods in enhancing the social-emotional skills of group B children at Parado Kindergarten. The study employs an action research approach organized in repeated cycles. Each cycle consists of four stages: planning, action implementation, observation, and reflection. The research subjects are the group B children at Parado Kindergarten, totaling 15 participants. Data collection methods include observation and documentation, with data analysis conducted using descriptive statistics. The data analysis reveals that in cycle 1, the children's social-emotional abilities reached a percentage of 50%. This figure indicates that the action research has not yet achieved the set target of 80%. Therefore, the research proceeds to cycle 2, which yielded a result of 97%, demonstrating the success of the study. These findings support the notion that the utilization of role-playing methods can effectively enhance the social-emotional skills of children.